Superheated steam treatment modulates lipid–volatile metabolomics associations and improves storage stability of highland barley (Qingke) - Mengjia Li; Yang Li; Bei Fan; Jingfeng Li; Zhangjing Lu; Fengzhong Wang; Lili Wang (Food Chemistry, 2026)

Generation and application of monoclonal antibodies against CD4-1 and CD8α for characterizing T cell subsets in grass carp (Ctenopharyngodon idella) - Haokai Chen; Ming Geng; Kang Li; Zhichao Fang; Yating Zhu; Yuqing Yang; Shiqi Tang; Jingfeng Ding; Jiansong Zhang; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2026)

Experimental and numerical investigation of shear buckling behaviour of friction stir welded 6013-T6 aluminium H-shaped beams - Beibei Li; Yanjun Tong; Boshan Chen; Jingfeng Wang; Hongzhuang Yang; Yihe Guo; Bingbing Sun (Engineering Structures, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Responses of evapotranspiration and gross primary productivity to extreme vapor pressure deficit, shortwave radiation, and soil moisture across China - Yi Liu; Jingfeng Xiao; Xing Li; Yue Li (Agricultural and Forest Meteorology, 2026)

Multifunctional aramid honeycombs filled with PVDF composite foams via in situ supercritical foaming: Nearly-isotropic broadband microwave absorption and mechanical reinforcement - Yang Ou; Hongbo Hou; Jingfeng He; Wenhan Cui; Jiaju Zhu; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2026)

Impact of age on safety of pancreaticoduodenectomy: a nationwide cohort study stratified by surgical approach and anastomotic technique with optimal age cut-off analysis - Hongwei Huang; Feng Xia; Tianyin Shao; Baiyong Shen; Xinmin Yin; Xiaoqing Jiang; Deyu Li; Jing Li; Sen Qiao; Songqing He; Heshui Wu; Jiayun Ge; et al. (Science China Life Sciences, 2026)

Mechanical evaluation of high-performance fiber ropes: creep test, tensile response and joint behavior - Beibei Li; Yanjun Tong; Yuanqing Wang; Shaomin Chen; Zongyi Wang; Jingfeng Wang; Zhe Wang; Quanxi Ye (Ocean Engineering, 2026)

UAV coarse visual localization in large-scale continuous scenes - Cheng Bi; Jingfeng Wang; Zhengxi Li; Yang Zhao; Zhiyu Jiang; Yuan Yuan; Ganchao Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Cynaroside reduces neutrophil extracellular trap formation and disease severity in a mouse model of asthma by inhibiting the COX-2/TNF-alpha/NF-kB axis - Daowen Yang; Jingfeng Liu; Qiao Wang; Jiawen Li; Chuanxi Tian; Ziqing Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Theory, application and prospect of full-life-cycle operation and maintenance technique system in coal underground water reservoir - Jiahui Song; Hanpeng Wang; Wei Wang; Bing Zhang; Wenqi Zheng; Yunhao Wu; Jingfeng Li; Jie Fang; Baoyang Wu; Zhengdai Li (Tunnelling and Underground Space Technology, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Masked ecological risk: Stable anammox performance conceals resistance genes propagation under short-term non-antibiotic antimicrobials stress - Qiyue Zuo; Jingfeng Gao; Jinming Zhang; Tianyi Lu; Ke Zhang; Ke Li; Feifei Gao; Yameng Wang; Yan Guo (Bioresource Technology, 2026)

N-acetylcysteine enhances antioxidant capacity and anti-bacterial immunity of T cells in tilapia by regulating KEAP1-NRF2 axis - Kang Li; Shiqi Tang; Jingfeng Ding; Yuqing Yang; Haokai Chen; Qiqi Jiang; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

Bio-electrochemical regulation of sulfur transformations for boosted sulfur-based denitrification and integrated sulfate abatement: Performance and mechanisms - Jingfeng Ding; Gaoming Wu; Dazhi Bai; Bin Yang; Yang Hou; Lecheng Lei; Zhongjian Li (Journal of Environmental Chemical Engineering, 2026)

Anammox-based Multi-pathway biological nitrogen removal for high ammonia nitrogen wastewater treatment: Rapid startup and community response in pilot-scale application under starvation strategy - Guangchao Si; Li Zhang; Jingfeng Gao; Shujun Zhang; Zhibin Wang; Xiaowu Huang; Yongzhen Peng (Environmental Research, 2026)

KLF9 Aggravates Doxorubicin-Induced Cardiotoxicity by Regulating the ROS/p53 Signalling Pathway - Jingfeng Peng; Jianhua Wang; Hui Feng; Bihan Zhou; Haoyu Zhou; Fangfang Li (Cardiovascular Toxicology, 2026)

Interfacial electronic reconstruction in Fe3O4-NiTe/NF heterostructures for efficient PET upcycling to high-value chemicals coupled with green hydrogen production - Peng Chen; Xinyuan Zhang; Chenyu Li; Yuqing Zhao; Xiaoqi Chen; Binni Wang; Jingfeng Wang (Chemical Engineering Journal, 2026)

Corrigendum to “NH2-MIL-101(Fe)-mediated photo-Fenton reaction enhanced simultaneous removal of nitrogen and refractory organics in anammox process through interfacial electron transfer” [Bioresour. Technol. 395 (2024) 130390] - Guangchao Si; Jiachun Yang; Li Zhang; Jingfeng Gao; Shujun Zhang; Shouqing Ni; Yongzhen Peng (Bioresource Technology, 2026)

Respiration‐Induced Weakening of Land Sink Contributed to the Largest CO 2 Increase in 2024 - Chaoya Dang; Zihua Shi; Josep Peñuelas; Philippe Ciais; Stephen Sitch; Jingfeng Xiao; Xing Li; Yanfeng Ding; Songhan Wang (Global Change Biology, 2026)
In 2024, the global annual growth rate of atmospheric CO 2 (CGR) surged to a record of 3.73 ppm year −1 —the highest since 1959—exceeding the 1.5°C climate threshold for the first time. However, the drivers behind this unprecedented rise remain poorly understood. Here, we employed a machine‐learning approach integrating satellite‐derived gross primary productivity (GPP) and climatic data to estimate the 2024 land sink (S LAND ) at approximately 2.21 ± 0.25 GtC year −1 , which had a striking decline of 1.01 GtC year −1 compared to the 2014–2023 average. The reduction in S LAND , most pronounced in tropical regions, contributed ~50% to the 2024 CGR increase—a larger impact than that of fossil fuel emissions or ocean sinks. Moreover, using partial least squares structural equation modelling, we further explained the underlying mechanism for the reduction of the S LAND in 2024, which was caused by hotter and drier conditions leading to a larger increase in respiration than photosynthesis. Our findings underscore the urgent need to investigate the mechanisms behind the declining carbon sink amid persistent global greening. These results challenge previous assumptions about the long‐term stability of the terrestrial carbon sink and highlight society's growing dependence on adaptive strategies to mitigate climate warming.

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Rapid and efficient inactivation of Pseudocohnilembus persalinus in aquaculture water using O3/H2O2 advanced oxidation technology - Yuwei Cui; Jingfeng Jia; Xiaojuan Shao; Wulong Jiang; Wenke Liu; Hua Wang; Ruijun Li; Zhongming Huo (Aquaculture International, 2026)

A multi-agent system for neighborhood-scale carbon simulation: Integrating intelligent multi-source sensing with interaction-driven modeling - Ao Sun; Xiucheng Zhai; Lefan Pian; Lu Li; Shuyuan Jia; Jingfeng Yuan; Shu Su (Sustainable Cities and Society, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Dual-mode regulation of cyclohexylamine biodegradation by dissolved oxygen: Metabolic trade-offs and community stability mechanisms - Cheng Qiu; Jingfeng Ding; Minwen Guo; Can Chen; Wenwu Zhang; Bin Yang; Yang Hou; Zhongjian Li (Journal of Water Process Engineering, 2026)

The trend and interannual variability in the global terrestrial evapotranspiration are respectively dominated by humid regions and drylands - Huiling Chen; Kun Zhang; Gaofeng Zhu; Lei Fan; Xin Li; Yunquan Wang; Xufeng Wang; Shasha Shang; Jia Jia; Yongtai Zhu; Jingfeng Xiao (Journal of Hydrology, 2026)

Metabolic exploration of glycogen accumulating organisms’ sludge with Candidatus Contendobacter in enhanced biological phosphorus removal - Shang Wang; Yuchao Liu; Yujie Cai; Xuan Wang; Bin Xue; Sheng Li; Yiqiu Fang; Chao Li; Jingfeng Wang (Journal of Environmental Sciences, 2026)

Experimental study on punching shear performance of embedded special-shaped CFST column base - Yong Liu; Zhuofei Li; Jingfeng Wang; Lanhui Guo; Fan Ye; Shasha Tan; Beibei Li (Engineering Structures, 2026)

Editor's note to “The Grain-for-Green project offsets warming-induced soil organic carbon loss and increases soil carbon stock in Chinese Loess Plateau” [Sci. Total Environ. 837 (2022), 155469] - Huiwen Li; Yiping Wu; Shuguang Liu; Wenzhi Zhao; Jingfeng Xiao; Leigh A. Winowiecki; Xiaowei Yin; Fan Wang; Bellie Sivakumar; Yue Cao; Pengcheng Sun (Science of The Total Environment, 2026)

High-sensitivity, multi-modal triboelectric sensor derived from Kevlar for self-powered Morse code transmission and human-machine interaction - Tao Huang; Zhaoqing Lu; Fengfeng Jia; Ruixue Pang; Huimei Zhao; Pengbo Yang; Chunting Li; Jingfeng Chen; Li Hua (Chemical Engineering Journal, 2026)

Preparation and digestive behavior of ferulic acid-bacterial cellulose/arabinoxylan complex with strong antioxidant activity - Xueqing Wang; Giorgia Purcaro; Yang Li; Jingjing Yang; Lang Jia; Jingfeng Li; Bei Fan; Yatao Huang; Fengzhong Wang; Lili Wang (Carbohydrate Polymers, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Enhanced T-cell activation and effector functions contribute to disease resistance in Streptococcus agalactiae-resistant tilapia - Ming Geng; Jingfeng Ding; Jun Xiao; Liting Chen; Jiansong Zhang; Kang Li; Jie Cheng; Yi Cao; Jialong Yang; Xiumei Wei (Aquaculture, 2026)

Satellite observations reveal ecosystem resistance and resilience to short-term water stress driven by dominant vegetation along a rainfall gradient in Australia - Huanhuan Wang; Qiaoyun Xie; Sally E. Thompson; Caitlin E. Moore; David L. Miller; Erik J. Veneklaas; Richard P. Silberstein; Xing Li; Jingfeng Xiao; Belinda E. Medlyn; William K. Smith (Remote Sensing of Environment, 2026)

Impacts of sodium benzoate and lysozyme on nitrification performance and resistance genes: Acute effects of single and co-exposure at different concentrations - Feifei Gao; Jingfeng Gao; Yameng Wang; Yan Guo; Ke Li; Qiyue Zuo; Tianyi Lu (Journal of Hazardous Materials, 2026)

Disentangling the climate–VPD–GPP Nexus: Global patterns and underlying drivers - Shanshan Chen; Jingfeng Xiao; Xing Li; Minchao Wu; Jie Yang (Global and Planetary Change, 2026)

Electrochemically assisted activation of peroxymonosulfate by Cu-Co bimetallic carbon nitride for enhanced deoxynivalenol degradation - Bingjie Wang; Xi Zhang; Zhixia Wu; Chenyu Li; Jingfeng Wang; Xu Han (Journal of Environmental Chemical Engineering, 2025)

Pre-occupation strategy towards high initial coulombic efficiency in Mn-based layer cathode for magnesium-based hybrid-ion batteries - Yipeng Liu; Baihua Qu; Junhao Zhang; Hongfei Zheng; Le Tong; Yue Hao; Dong Wang; Guangsheng Huang; Qian Li; Xiaoyuan Zhou; Dong-Liang Peng; Jingfeng Wang (Chemical Engineering Journal, 2025)

Stress-Permeability Modeling of Sandstone Using Wave Velocity-Based Porosity Evolution - Zhengdai Li; Jianping Zuo; Jingfeng Li; Yunjiang Sun; Meilu Yu; Yong Zhang; Baoyang Wu (Geotechnical and Geological Engineering, 2025)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

Impact of large-scale climate indices on total nitrogen concentrations in drinking water sources cannot be overlooked - Ning Li; Jingfeng Xiao; Zheng Zhang; Rui Bai; Jiayi Yong; Ziyu Ning; Miao Chen; Yaxiong Chen; Shuli Xin; Shengwu Xiong (Journal of Hydrology, 2025)

Explore the relationship between Bowen ratio and evapotranspiration in wetlands using the maximum entropy production model - Huaiwei Sun; Leying Fu; Weiguang Wang; Jie Xue; Jing Wang; Weihong Liao; Haicheng Li; Xunlai Sun; Yong Yang; Jingfeng Wang; Hong Zhang; Fulong Chen; et al. (Journal of Hydrology, 2025)

Radical-free ultra-rapid disinfection: Application of the periodate/Mn(II) system in eliminating antibiotic-resistant bacteria and genes and degrading emerging contaminants - Yameng Wang; Jingfeng Gao; Yan Guo; Lei Wei; Ying Liu; Feifei Gao; Qiyue Zuo; Ke Li (Journal of Hazardous Materials, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Mechanical analysis of eccentrically loaded SFRC columns reinforced by high-strength rebars: Testing and FE modelling - Ziming Hu; Jingfeng Wang; Qihan Shen; Beibei Li; Yong Liu (Engineering Structures, 2025)

Spider web-inspired ZIF@PPy conductive networks for efficient flow-electrode capacitive desalination of high-salinity antibiotic wastewater - Huachun Pan; Jingfeng Ding; Shuangwei Chen; Zhikang Li; Zhikan Yao; Chen Sun; Yang Hou; Zhongjian Li; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2025)

Net ecosystem exchange of CO2 and its driving mechanisms in an island forest nature reserve in southern China - Liangxu Wu; Shuya Xie; Xianglan Li; Pengpeng Tian; Zhe Xu; Yuting Huang; Jingfeng Xiao; Xintong Chen; Minghai Xu; Wei Chen; Houcai Cai (CATENA, 2025)

The impact of selenium fertilizer application on the yield, quality, and selenium accumulation characteristics of sweet potato - Huifeng Li; Yixuan Zhang; Yanqing Li; Yongmei Huang; Jingfeng Hua; Jie Yin; Dong Xiao; Tianyuan Chen (Acta Physiologiae Plantarum, 2025)

Inconsistencies in global soil moisture products and discrepancies in their relationship with vegetation productivity - Xinyao Xu; Xufeng Wang; Jingfeng Xiao; Songlin Zhang; Yanpeng Yang; Xing Li; Te Sha; Zongxing Li (Journal of Hydrology, 2025)

Identification of the deterioration flavor markers based on E-nose, GC-IMS and GC–MS during fresh sea cucumber storage and preservation by thymol - Jinghe Sun; Weiyun Zheng; Xiaoyan Wang; Yimeng Li; Jingfeng Yang (Food Chemistry, 2025)

Gradient multi-component interphase enabling highly reversible magnesium metal anode in fluorinated alkoxyborate-based electrolytes - Yuhang Chen; Yiming Zhang; Zhimeng Tang; Zhenyu Zhang; Le Tong; Xuemin Gan; Xing Shen; Guangsheng Huang; Qian Li; Baihua Qu; Fusheng Pan; Jingfeng Wang (Chemical Engineering Journal, 2025)

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

The Sustained-Release Oxygen Granule Preparation and Its Application in the Transportation of Live Sea Cucumber Apostichopus Japonicus - Yimeng Li; Jinghe Sun; Yan Zhou; Liming Sun; Jingfeng Yang (Journal of Aquatic Food Product Technology, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

A data-driven and knowledge graph-based research on safety risk-coupled evolution analysis and assessment in shield tunneling - Xuewei Li; Shuchen Li; Jingfeng Yuan; Zeen Wan; Xuan Liu (Tunnelling and Underground Space Technology, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Unveiling uncertainties in soil organic carbon modeling: the critical role of climate response functions - Huiwen Li; Yue Cao; Jingfeng Xiao; Wenxin Zhang; Yiping Wu; Arshad Ali; Zuoqiang Yuan (Environmental Modelling & Software, 2025)

Numerical analysis and calculation methods on the axial-loaded compressive behavior of cross-shaped partially encased concrete composite columns - Shuqing Tao; Yong Liu; Jingfeng Wang; Peng Gao; Qijun Yu; Qiuyu Xu; Jingzhe Li (Engineering Structures, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Edible nano-film incorporated with lemon essential oil-loaded Pickering emulsion for cold storage improvement of Penaeus vannameia - Yimeng Li; Jinghe Sun; Chunqing Ai; Shuang Song; Jingfeng Yang (Food Bioscience, 2025)

Pilot-scale application of sludge fermentation-driven nitrogen removal process with rapid in-situ enrichment of anammox bacteria for sustainable treatment of municipal wastewater and excess sludge - Shiwei Hao; Li Zhang; Jingfeng Gao; Xuepeng Fan; Tingjun Dong; Jiachun Yang; Shuang Lan; Yongzhen Peng (Chemical Engineering Journal, 2025)

Microplastics enhance the denitrification of glycogen-accumulating organisms by regulating electronic transport in carbon-nitrogen coupling - Yuchao Liu; Jinrui Cao; Sheng Li; Xinxin He; Bin Zhang; Shang Wang; Jingfeng Wang (Journal of Hazardous Materials, 2025)

High-efficiency recovery of FePO4 from lithium extraction slag via SO2 reductive leaching and selective precipitation - Jie Li; Jiang Diao; Zhiqiu Lai; Hong-Yi Li; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Journal of Cleaner Production, 2025)

The influence mechanism of environmental factors on DGT adsorbing sulfonamides and the migration between water and sediment - Peng Zhang; Jingfeng Yan; Hao Ji; Linke Ge; Yanying Li (Journal of Environmental Sciences, 2025)

Novel polymer electrolytes for rechargeable magnesium batteries prepared based on deep eutectic solvents - Peng Yang; Xiaoping Liang; Yu Wang; Li Gao; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Chemical Engineering Journal, 2025)

Impacts of meteorological drought on peak vegetation productivity of grasslands from perspectives of canopy structure and leaf physiology - Wenrui Bai; Huanjiong Wang; Jingfeng Xiao; Xing Li; Quansheng Ge (International Journal of Biometeorology, 2025)

Integrated Proteomics and Metabolomics Analyses Reveal Molecular Mechanism of Cardiac Resynchronization Therapy Against Cardiac Fibrosis and Ventricular Arrhythmias - Maoxiong Wu; Haiying Li; Jing Tan; Jingting Mai; Shaoxin Zheng; Qiong Qiu; Bingqing Deng; Hanlu Lv; Peiwei Wang; Jingfeng Wang; Yangxin Chen; Woliang Yuan (Cardiovascular Toxicology, 2025)

Heat Deficit for Vegetation Leaf Senescence and Its Key Accumulation Process and Determinants at Northern Middle and High Latitudes During 2001–2022 - Zhihui Yuan; Gang Bao; Fei Li; Jiquan Chen; Jingfeng Xiao; Qier Mu; Enliang Guo; Siqin Tong; Sainbuyan Bayarsaikhan (Global Ecology and Biogeography, 2025)
Aim Cold degree days (CDD) represent the heat deficit for vegetation leaf senescence in autumn and serve as a critical parameter in modelling leaf senescence. This study aimed to quantify the spatiotemporal patterns of CDD and its key accumulation processes and determinants. Location At northern middle and high latitudes (> 30° N). Period 2001–2022. Major Taxa Studied Vegetation. Methods We estimate CDD as the cumulative sum of the difference between the daily mean temperature and a threshold temperature (12.75°C) during the period from midsummer to the end of the growing season. To identify its crucial metric, we employ a combination of grey relational analysis, random forest model and partial correlation analysis. Results The average CDD increases linearly with latitude at a rate of 5.9°C‐days per degree. Higher latitudes exhibit larger CDD (> 300.0°C‐days), longer accumulation periods (> 70 days) and faster accumulation rates (> 6.0°C/day), whereas lower latitudes show smaller CDD ( 46% of the study area, especially at high latitudes and on the Tibetan Plateau. While climate warming generally reduces CDD, an increase in precipitation frequency can counteract this trend and shape the relationship between precipitation amount and CDD. The effects of radiation and wind speed on CDD were less pronounced than those of precipitation frequency, with wind exerting a positive (cooling) effect that increases CDD accumulation and radiation producing a negative (heating) effect that decreases CDD accumulation. Main Conclusions This study highlights the critical aspects of the CDD accumulation process and emphasises the importance of incorporating precipitation frequency into CDD‐based autumn phenology models across northern latitudes.

Importance of viewing angle: Hotspot effect improves the ability of satellites to track terrestrial photosynthesis - Haoran Liu; Jingfeng Xiao; Dalei Hao; Fa Li; Fujiang Ji; Min Chen (Remote Sensing of Environment, 2025)

Relic DNA obscures bacterial diversity and interactions in ballast tank sediment - Zhaozhao Xue; Haoze He; Yangchun Han; Wen Tian; Shengjie Li; Jingfeng Guo; Pei Yu; Lina Qiao; Wei Zhang (Environmental Research, 2025)

TG-Net: A Physically Interpretable Deep Learning Forecasting Model for Thunderstorm Gusts - Yunqing Liu; Lu Yang; Mingxuan Chen; Jianwei Si; Maoyu Wang; Wenyuan Li; Jingfeng Xu (Journal of Meteorological Research, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Interactive and dynamic insights into environmental impacts of a neighborhood: A tight coupling of multi-agent system and dynamic life cycle assessment - Shu Su; Jingyi Ju; Jingfeng Yuan; Yuan Chang; Qian Li (Environmental Impact Assessment Review, 2025)

Process optimization study on single atom solutions for CO2 capture and methanation based on experiment and simulation - Yuan Li; Jingfeng Zhang; Yunsong Yu; Zaoxiao Zhang (Chemical Engineering Journal, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Rising Atmospheric CO 2 Alleviates Drought Impact on Autumn Leaf Senescence Over Northern Mid‐High Latitudes - Peng Li; Mai Sun; Jingfeng Xiao; Yunpeng Luo; Yao Zhang; Xing Li; Xiaolu Zhou; Changhui Peng (Global Ecology and Biogeography, 2025)
Aim Drought reduces plant growth and hastens the process of leaf senescence in autumn. Concurrently, increasing atmospheric CO 2 concentrations likely amplifies photosynthetic activity while increasing plant water‐use efficiency. However, how drought affects the date of leaf senescence (DLS) and whether elevated CO 2 can alleviate this remain unknown. Here, we explore the effect of drought on DLS under recent climate change and explore the underlying mechanisms. Location Northern mid‐high latitudes. Time Period 2000–2019. Major Taxa Studied Plants. Methods We conducted comprehensive analyses based on satellite remote sensing, eddy covariance flux observations, in situ phenology observations and land‐surface models. Linear regression analysis and a ten‐year moving window were adapted to investigate the spatiotemporal patterns in DLS sensitivity to drought ( S dd ). The partial least squares regression method was used to attribute the main factors for the variation in S dd , and land‐surface models in different scenarios were used to verify the robustness of the results. Results Our study presented divergent spatial patterns of S dd , where the highest S dd was concentrated in dry and warm regions. Temporally, multiple datasets consistently illustrate a significant decrease in the S dd during recent decades ( p S dd and aridity gradient, which presented a slightly positive S dd trend in dry regions but a negative trend in wet regions. We found these observed changes were primarily attributed to elevated CO 2 , alleviating the drought stress on DLS in nearly 40% of the study area. Main Conclusions Our findings demonstrate the complex role that atmospheric CO 2 plays in regulating plant leaf senescence during drought stress, highlighting the need to incorporate the effects of elevated CO 2 on vegetation autumn phenology into land‐surface models for projecting vegetation growth and carbon uptake under continued global change.

Environmental RNA metabarcoding for ballast water microbial diversity: Minimizing false positives - Zhaozhao Xue; Wen Tian; Yangchun Han; Shengjie Li; Jingfeng Guo; Haoze He; Pei Yu; Wei Zhang (Science of The Total Environment, 2024)

Nitrogen are the main factors driving the structure and function of the marine archaeal community in Yongle Blue Hole, Sansha - Wenjing Wang; Hongxia Ming; Dongwei Li; Yuan Jin; Yuyang Xie; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Enhancing Fenton-like reaction mediating performance of covalent organic frameworks through porosity modification - Guangchao Si; Li Zhang; Jingfeng Gao; Jiachun Yang; Akira Miyazawa; Yongzhen Peng (Environmental Research, 2024)

Spinach leaf disease identification based on deep learning techniques - Laixiang Xu; Jingfeng Su; Bei Li; Yongfeng Fan; Junmin Zhao (Plant Biotechnology Reports, 2024)

Alterations in feeding preference and gastric emptying of giant freshwater prawn (Macrobrachium rosenbergii) following administration of varying quantities of fermented soybean meal - XingHui Cai; Jingyi Luo; Xiang Li; JingFeng Yang; XueMing Hua; Tao Liu (Aquaculture International, 2024)

Genomic synergistic efficient carbon fixation and nitrogen removal induced by excessive inorganic carbon in the anammox-centered coupling system - Shiwei Hao; Li Zhang; Jingfeng Gao; Tingjun Dong; Yongzhen Peng; Akira Miyazawa (Water Research, 2024)

Residual stress tests and predictive model of friction stir welded normal-strength aluminium alloy H-shaped sections - Beibei Li; Guoqiang Li; Jingfeng Wang; Boshan Chen; Yuanqing Wang; Yecheng Dai; Gang Dong (Engineering Structures, 2024)

HMS optical fiber gas sensor based on double-layer WO3@CQDs porous film modified cladding for detecting 2-butanone gas at room temperature - Yan-nan Wang; Jingfeng Li; Zhiqiang Yang; Zhenyu Yuan; Jin Li; Fanli Meng (Chemical Engineering Journal, 2024)

Habitat quality evaluation and pattern simulation of coastal salt marsh wetlands - Yuting Huang; Guanghui Zheng; Xianglan Li; Jingfeng Xiao; Zhe Xu; Pengpeng Tian (Science of The Total Environment, 2024)

A machine learning scheme for estimating fine-resolution grassland aboveground biomass over China with Sentinel-1/2 satellite images - Huaqiang Li; Fei Li; Jingfeng Xiao; Jiquan Chen; Kejian Lin; Gang Bao; Aijun Liu; Guo Wei (Remote Sensing of Environment, 2024)

Surface iso-transformation and floatability of calcite and fluorite - Xu Yang; Yubiao Li; Jingfeng Chen; Peng Chen; Shunxin Xie; Shaoxian Song (Minerals Engineering, 2024)

Global convergence in terrestrial gross primary production response to atmospheric vapor pressure deficit - Chao Huang; Jingfeng Huang; Jingfeng Xiao; Xing Li; Hong S. He; Yu Liang; Fusheng Chen; Hanqin Tian (Science China Life Sciences, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

Teacher-student guided knowledge distillation for unsupervised convolutional neural network-based speckle tracking in ultrasound strain elastography - Tianqiang Xiang; Yan Li; Hui Deng; Chao Tian; Bo Peng; Jingfeng Jiang (Medical & Biological Engineering & Computing, 2024)

Snow cover duration delays spring green-up in the northern hemisphere the most for grasslands - Xufeng Wang; Zongxing Li; Jingfeng Xiao; Gaofeng Zhu; Junlei Tan; Yang Zhang; Yingchun Ge; Tao Che (Agricultural and Forest Meteorology, 2024)

A cell-free fluorescence biosensor based on allosteric transcription factor NalC for detection of pentachlorophenol - Shuting Chen; Chen Zhao; Xiaodan Kang; Xi Zhang; Bin Xue; Chenyu Li; Shang Wang; Xiaobo Yang; Chao Li; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Biotechnology Letters, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

Significantly enhanced biodegradation of profenofos by Cupriavidus nantongensis X1T mediated by walnut shell biochar - Genrong Zhang; Jingfeng Xue; Yufei Zhang; Jia Ye; Nan Zhang; Liancheng Fang; Taozhong Shi; Xin Ma; Hui Li; Rimao Hua (Journal of Hazardous Materials, 2024)

Enhancing thermoelectric performance in GeTe through Ge enrichment regulation and AgCuTe alloying - Jingyi Lyu; Jingfeng Li; Wenwei Yang; Zhixing Chen; Zijie Ren; Zhanpeng Zhao; Shenghua Liu; Jing Shuai (Chemical Engineering Journal, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Contrasting responses of relationship between solar-induced fluorescence and gross primary production to drought across aridity gradients - Ruonan Qiu; Ge Han; Xing Li; Jingfeng Xiao; Jiangong Liu; Songhan Wang; Siwei Li; Wei Gong (Remote Sensing of Environment, 2024)

Establishing the global isoscape of leaf carbon in C3 plants through the integrations of remote sensing, carbon, geographic, and physiological information - Xiang Wang; Guo Chen; Joseph Awange; Yongze Song; Qi Wu; Xiaowei Li; Edmund February; Gustavo Saiz; Ralf Kiese; Xing Li; Jingfeng Xiao; Xiaoxiang Zhao; et al. (Remote Sensing of Environment, 2024)

Soil moisture retrieval by a novel hybrid model based on CYGNSS and Sun-induced fluorescence data - Yan Li; Songhua Yan; Jianya Gong; Jingfeng Xiao; Milad Asgarimehr; Jens Wickert (Journal of Hydrology, 2024)

Impact of the Three Gorges Dam on hydrological connectivity and vegetation growth of Poyang Lake floodplain, China - Jinfeng Zeng; Jingfeng Qiu; Zeyu Wu; Xinggen Liu; Yunliang Li (Journal of Hydrology, 2024)

Metabolic shifts in glycogen-accumulating organisms: Exploring carbon and phosphorus dynamics under two distinct phosphorus limitation modes - Shang Wang; Chenyu Li; Chunchun Zhang; Yuchao Liu; Sheng Li; Yiqiu Fang; Zhiqiang Shen; Jingfeng Wang (Journal of Cleaner Production, 2024)

NH2-MIL-101(Fe)-mediated photo-Fenton reaction enhanced simultaneous removal of nitrogen and refractory organics in anammox process through interfacial electron transfer - Guangchao Si; Jiachun Yang; Li Zhang; Jingfeng Gao; Shujun Zhang; Shouqing Ni; Yongzhen Peng (Bioresource Technology, 2024)

Assessment of methane emissions from pressure regulation stations in China - Fei Li; Jianfeng Tang; Zhengyi Xie; Xuanke Li; Yuchen Niu; Tong Li; Yifan Wang; Jingfeng Zhang; Zhenyu Gao (Atmospheric Pollution Research, 2024)

Polymer surfactants as viscosity reducers for ultra-heavy oil: Synthesis and viscosity reduction mechanism - Xiaojun Zhang; Jixiang Guo; Dongtao Fei; Li Wang; Zhongying Peng; Jianmin Li; Jingfeng Dong (Fuel, 2024)

Multidrug-resistant plasmid RP4 inhibits the nitrogen removal capacity of ammonia-oxidizing archaea, ammonia-oxidizing bacteria, and comammox in activated sludge - Zhaohui Zhang; Lin Bo; Shang Wang; Chenyu Li; Xi Zhang; Bin Xue; Xiaobo Yang; Xinxin He; Zhiqiang Shen; Zhigang Qiu; Chen Zhao; Jingfeng Wang (Environmental Research, 2024)

Plant community diversity alters the response of ecosystem multifunctionality to multiple global change factors - Zhenwei Xu; Xiao Guo; Warwick J. Allen; Xiaona Yu; Yi Hu; Jingfeng Wang; Mingyan Li; Weihua Guo (Global Change Biology, 2024)
Biodiversity is considered important to the mitigation of global change impacts on ecosystem multifunctionality in terrestrial ecosystems. However, potential mechanisms through which biodiversity maintains ecosystem multifunctionality under global change remain unclear. We grew 132 plant communities with two levels of plant diversity, crossed with treatments based on 10 global change factors (nitrogen deposition, soil salinity, drought, plant invasion, simulated grazing, oil pollution, plastics pollution, antibiotics pollution, heavy metal pollution, and pesticide pollution). All global change factors negatively impacted ecosystem multifunctionality, but negative impacts were stronger in high compared with low diversity plant communities. We explored potential mechanisms for this unexpected result, finding that the inhibition of selection effects (i.e., selection for plant species associated with high ecosystem functioning) contributed to sensitivity of ecosystem multifunctionality to global change. Specifically, global change factors decreased the abundance of novel functional plants (i.e., legumes) in high but not low diversity plant communities. The negative impacts of global change on ecosystem multifunctionality were also mediated by increased relative abundance of fungal plant pathogens (identified from metabarcoding of soil samples) and their negative relationship with the abundance of novel functional plants. Taken together, our experiment highlights the importance of protecting high diversity plant communities and legumes, and managing fungal pathogens, to the maintenance of ecosystem multifunctionality in the face of complex global change.

Monitoring diurnal dynamics of surface urban heat island for urban agglomerations using ECOSTRESS land surface temperature observations - Yue Chang; Jingfeng Xiao; Xuxiang Li; Qihao Weng (Sustainable Cities and Society, 2023)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Marine toxin domoic acid alters protistan community structure and assembly process in sediments - Zelong Li; Jing Wang; Jingfeng Fan; Hao Yue; Xiuhong Zhang (Marine Environmental Research, 2023)

Graphite carbon nitride photocatalytic materials: A roadmap to modification for current and future water purification - Xinyuan Zhang; Chenyu Li; Lin Dai; Chuanling Si; Zhiqiang Shen; Zhigang Qiu; Jingfeng Wang (Journal of Environmental Chemical Engineering, 2023)

AIEgen-based nanotherapeutic strategy for enhanced FLASH irradiation to prevent tumour recurrence and avoid severe side effects - Meng Lyu; Tianfu Zhang; Yang Li; Jingfeng Xiang; Daoming Zhu; Ligang Xia; Bin Guo; Youhua Xu; Haijun Yu; Benzhong Tang (Chemical Engineering Journal, 2023)

Oxygenated storage alleviates autolysis of the sea cucumber Apostichopus japonicus during transport - Yan Zhou; Jie Zheng; Jun Zhao; Shuang Li; Jie Xing; Chunqing Ai; Chenxu Yu; Sheng Yang; Jingfeng Yang (Aquaculture International, 2023)

The knock-on effects of different wastewater feeding modes: Change in microbial communities versus resistance genes in pilot-scale aerobic sludge granulation reactors - Yi Guo; Dingchang Li; Yongqing Gao; Jingfeng Gao; Shujun Zhang; Fangbo Bao (Science of The Total Environment, 2023)

A comprehensive review of calcium and ferrous ions chelating peptides: Preparation, structure and transport pathways - Qiaoji Tian; Yan Fan; Li Hao; Jie Wang; Chensi Xia; Jingfeng Wang; Hu Hou (Critical Reviews in Food Science and Nutrition, 2023)

Multidrug-resistant plasmid RP4 increases NO and N2O yields via the electron transport system in Nitrosomonas europaea ammonia oxidation - Jia Li; Chen Zhao; Chenyu Li; Bin Xue; Shang Wang; Xi Zhang; Xiaobo Yang; Zhiqiang Shen; Lin Bo; Xinxin He; Zhigang Qiu; Jingfeng Wang (Water Research, 2023)

Solar-induced chlorophyll fluorescence detects photosynthesis variations and drought effects in tropical rubber plantation and natural deciduous forests - Xueqian Wang; Peter D. Blanken; Jeffrey D. Wood; Yann Nouvellon; Philippe Thaler; Poonpipope Kasemsap; Amnat Chidthaisong; Pakorn Petchprayoon; Chompunut Chayawat; Jingfeng Xiao; Xing Li (Agricultural and Forest Meteorology, 2023)

Large discrepancies among remote sensing indices for characterizing vegetation growth dynamics in Nepal - Decheng Zhou; Liangxia Zhang; Lu Hao; Ge Sun; Jingfeng Xiao; Xing Li (Agricultural and Forest Meteorology, 2023)

Accident pattern recognition in subway construction for the provision of customized safety measures - Haonan Qi; Zhipeng Zhou; Jingfeng Yuan; Nan Li; Jianliang Zhou (Tunnelling and Underground Space Technology, 2023)

Biomimetic single-atom nanozyme system for efficient inhibition of gastric cancer ascites via SO2 gas-enhanced nanocatalytic cancer therapy - Tao Chen; Xi Luo; Liwei Zhu; Jingfeng Xiang; Chuanfa Fang; Daoming Zhu; Guoxin Li; Yanhong Duo (Chemical Engineering Journal, 2023)

Pheromone effect of estradiol regulates the conjugative transfer of pCF10 carrying antibiotic resistance genes - Xiaobo Yang; Yuanyuan Niu; Yutong Yang; Hongrui Zhou; Jing Li; Xinyue Fu; Zhiqiang Shen; Jingfeng Wang; Zhigang Qiu (Journal of Hazardous Materials, 2023)

Carbon exchange of forest plantations: global patterns and biophysical drivers - Xiaojuan Tong; Jingfeng Xiao; Peirong Liu; Jinsong Zhang; Jingru Zhang; Peiyang Yu; Ping Meng; Jun Li (Agricultural and Forest Meteorology, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Growth of grasses and forbs, nutrient concentration, and microbial activity in soil treated with microbeads - Jingfeng Wang; Xiao Guo; Janice Brahney; Zhenwei Xu; Yi Hu; Wenyi Sheng; Yanni Chen; Mingyan Li; Weihua Guo (Environmental Pollution, 2023)

Mitigating the inhibition of antibacterial agent chloroxylenol on nitrification system-The role of Rhodococcus ruber in a bioaugmentation system - Yi Guo; Jingfeng Gao; Yifan Zhao; Ying Liu; Mingyan Zhao; Ziqiao Li (Journal of Hazardous Materials, 2023)

Label-free proteomics analysis on the envelope of budded viruses of Bombyx mori nucleopolyhedrovirus harboring differential localized GP64 - Bifang Hao; Jingfeng Li; Congcong Sun; Jinshan Huang (Virus Genes, 2023)

Biological control efficacy of Bacillus licheniformis HG03 against soft rot disease of postharvest peach - Xiaoli Wang; Jingfeng Zhu; Huan Wei; Zhipeng Ding; Xiran Li; Zao Liu; Hongbao Wang; Yunpeng Wang (Food Control, 2023)

Work along both lines: The p-chloro-m-cresol achieved stable and long-term partial nitrification and inhibited the enrichment of resistance genes - Yi Guo; Jingfeng Gao; Zejie Wu; Ziqiao Li; Yi Zhang; Haoran Zhang (Chemical Engineering Journal, 2023)

The spread of different resistance genes fractions in nitrification system under chronic exposure to varying alkyl chain length benzalkyl dimethylammonium compounds - Haoran Zhang; Jingfeng Gao; Mingyan Zhao; Zhiqi Wang; Dingchang Li; Zejie Wu; Yi Zhang; Ying Liu (Bioresource Technology, 2023)

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Intermittent ultrasound retains cellulases unlock for enhanced cellulosic ethanol with high-porosity biochar for dye adsorption using desirable rice mutant straw - Zhen Hu; Qian Li; Yuanyuan Chen; Tianqi Li; Youmei Wang; Ran Zhang; Hao Peng; Hailang Wang; Yanting Wang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Different acesulfame potassium fate and antibiotic resistance propagation pattern in nitrifying and denitrifying sludge systems - Ziqiao Li; Jingfeng Gao; Yifan Zhao; Zhiqi Wang; Yingchao Cui; Dingchang Li; Yi Guo; Zejie Wu; Liqin Zeng (Science of The Total Environment, 2023)

Partial S(0)-driven autotrophic denitrification process facilitated the quick natural enrichment of anammox bacteria at room temperature - Zhiqi Wang; Jingfeng Gao; Huihui Dai; Yukun Yuan; Yifan Zhao; Dingchang Li; Yingchao Cui (Science of The Total Environment, 2023)

Cation-π interaction in Mg(OH)2@GO-coated activated carbon fiber cloth for rapid removal and recovery of divalent metal cations by flow-through adsorption - Xiao Wang; Jingfeng Li; Qiang Guo; Menglan Xu; Xiaohan Zhang; Tong Li (Resources, Conservation and Recycling, 2023)

Cyclohexanecarboxylic acid degradation with simultaneous nitrate removal by Marinobacter sp. SJ18 - Shuaijun Zan; Jing Wang; Jingfeng Fan; Yuan Jin; Zelong Li; Miaomiao Du (Environmental Science and Pollution Research, 2022)

16S Next-generation sequencing and quantitative PCR reveal the distribution of potential pathogens in the Liaohe Estuary - Huiling Huang; Shuaijun Zan; Hongxia Ming; Mengfei Li; Jianrong Xu; Yuyang Xie; Wenjing Wang; Jingfeng Fan (Frontiers in Marine Science, 2022)
The existence of potentially pathogenic bacteria seriously threatens aquatic animals and human health. Estuaries are closely related to human activities, and the detection of pathogens is important for aquaculture and public health. However, monitoring only indicator microorganisms and pathogens is not enough to accurately and comprehensively estimate water pollution. Here, the diversity of potentially pathogenic bacteria in water samples from the Liaohe estuary was profiled using 16S next-generation sequencing (16S NGS) and quantitative polymerase chain reaction (qPCR) analysis. The results showed that the dominant genera of environmental pathogens were Pseudomonas , Vibrio , Mycobacterium , Acinetobacter , Exiguobacterium , Sphingomonas , and Legionella , and the abundance of enteric pathogens was significantly less than the environmental pathogens, mainly, Citrobacter , Enterococcus , Escherichia-Shigella , Enterobacter , Bacteroides . The qPCR results showed that the 16S rRNA genes of Vibrio were the most abundant, with concentrations between 7.06 and 9.48 lg copies/L, followed by oaa gene, fliC gene, trh gene, and uidA gene, and the temperature and salinity were the main factors affecting its abundance. Variance partitioning analysis (VPA) analysis of spatial factors on the potential pathogen’s distribution (19.6% vs 5.3%) was greater than environmental factors. In addition, the co-occurrence analysis of potential pathogens in the estuary revealed significant co-occurrence among the opportunistic pathogens Testosteronemonas , Brevimonas vesicularis , and Pseudomonas putida . Our findings provide an essential reference for monitoring and occurrence of potentially pathogenic bacteria in estuaries.

Divergent responses of autumn vegetation phenology to climate extremes over northern middle and high latitudes - Mei Wang; Peng Li; Changhui Peng; Jingfeng Xiao; Xiaolu Zhou; Yunpeng Luo; Cicheng Zhang (Global Ecology and Biogeography, 2022)
Aim Compared with gradual climate change, extreme climatic events have more direct and dramatic impacts on vegetation growth. However, the influence of climate extremes on important phenological periods, such as the end of the growing season (EOS), remains unclear. Here, we investigate the temporal trends of EOS across different biomes and quantify the response of EOS to multiple climate extreme indices (CEIs). Location Northern middle and high latitudes. Time period 2000–2020. Major taxa studied Plants. Methods Three phenology extraction methods were used to compute EOS from satellite, FLUXNET and Pan European Phenology Project PEP725 phenological datasets. Different stress states of cold, hot, dry and wet extremes were represented by 12 CEIs. Partial correlation and ridge regression analysis were used to quantify the response of EOS to climate extremes across latitudinal and biome scales. Results Our study showed a delayed EOS in boreal biomes, but a significantly advanced EOS in temperate biomes. The advanced EOS induced by cold stress was observed for c . 80% of the vegetated pixels. The warm‐related CEIs delayed the EOS in high latitudes, and the delayed effect weakened or even reversed with decreasing latitude. In contrast, EOS exhibited opposite response patterns to dry days and wet‐related CEIs. Overall, EOS exhibited higher sensitivity to extreme temperature in boreal biomes than in temperate biomes. Specifically, continuous drought and high heat stress induced an earlier EOS in some temperate forest biomes, whereas moderate heat stress delayed the EOS in most study biomes. In contrast, EOS was not sensitive to extreme drought in water‐restricted biomes. Main conclusions EOS exhibited divergent responses to various climate extremes with different intensities and frequencies. Moreover, the response of EOS to extreme climate stress was dependent on the biome and latitude. These findings emphasize the importance of incorporating the divergent extreme climate effects into vegetation phenological models and Earth system models.

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Rapid detection method of Skeletonema pseudocostatum and preparation of test strip - Haoran Li; Kun Meng; Qiaojie Yu; Changping Chen; Jingfeng Chen; Jingli Li; Xinyi Wang; Yingzi Wang; Mingyang Li; Chuang Chen; Kefu Zhou (Environmental Science and Pollution Research, 2022)

Aberrant DNA methylation in t(8;21) acute myeloid leukemia - Shujiao He; Jingfeng Zhou; Li Yu (Genome Instability & Disease, 2022)
Aberrant DNA methylation is a hallmark of acute myeloid leukemia (AML). Various studies showed that t(8;21) AML presented a distinct DNA methylation profile and could be categorized into a separate cluster according to DNA methylation sequencing. Yet, there is still a lack of understanding regarding the causes and mechanisms of this phenomenon. Knowing how the DNA methylation is regulated in t(8;21) AML would enhance our understanding of leukemogenesis and may assist clinical decision-making regarding DNA methylation-targeted therapy. Herein, we summarized our current knowledge concerning DNA methylation regulation in t(8;21) AML and discussed their potential clinical significance in this article.

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Monitoring and evaluation of antibiotic resistance genes in three rivers in northeast China - Chen Zhao; Chenyu Li; Xiaoming Wang; Zhuosong Cao; Chao Gao; Sicong Su; Bin Xue; Shang Wang; Zhigang Qiu; Jingfeng Wang; Zhiqiang Shen (Environmental Science and Pollution Research, 2022)

Decipher soil organic carbon dynamics and driving forces across China using machine learning - Huiwen Li; Yiping Wu; Shuguang Liu; Jingfeng Xiao; Wenzhi Zhao; Ji Chen; Georgii Alexandrov; Yue Cao (Global Change Biology, 2022)
The dynamics of soil organic carbon (SOC) play a critical role in modulating global warming. However, the long‐term spatiotemporal changes of SOC at large scale, and the impacts of driving forces remain unclear. In this study, we investigated the dynamics of SOC in different soil layers across China through the1980s to 2010s using a machine learning approach and quantified the impacts of the key factors based on factorial simulation experiments.Our results showed that the latest (2000–2014) SOC stock in the first meter soil (SOC 100 ) was 80.68 ± 3.49 Pg C, of which 42.6% was stored in the top 20 cm, sequestrating carbon with a rate of 30.80 ± 12.37 g C m −2 yr −1 since the 1980s. Our experiments focusing on the recent two periods (2000s and 2010s) revealed that climate change exerted the largest relative contributions to SOC dynamics in both layers and warming or drying can result in SOC loss. However, the influence of climate change weakened with soil depth, while the opposite for vegetation growth. Relationships between SOC and forest canopy height further confirmed this strengthened impact of vegetation with soil depth and highlighted the carbon sink function of deep soil in mature forest. Moreover, our estimates suggested that SOC dynamics in 71% of topsoil were controlled by climate change and its coupled influence with environmental variation (CE). Meanwhile, CE and the combined influence of climate change and vegetation growth dominated the SOC dynamics in 82.05% of the first meter soil. Additionally, the national cropland topsoil organic carbon increased with a rate of 23.6 ± 7.6 g C m −2 yr −1 since the 1980s, and the widely applied nitrogenous fertilizer was a key stimulus. Overall, our study extended the knowledge about the dynamics of SOC and deepened our understanding about the impacts of the primary factors.

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Seasonal changes in GPP/SIF ratios and their climatic determinants across the Northern Hemisphere - Anping Chen; Jiafu Mao; Daniel Ricciuto; Dan Lu; Jingfeng Xiao; Xing Li; Peter E. Thornton; Alan K. Knapp (Global Change Biology, 2021)
Satellite‐derived sun‐induced chlorophyll fluorescence (SIF) has been increasingly used for estimating gross primary production (GPP). However, the relationship between SIF and GPP has not been well defined, impeding the translation of satellite observed SIF to GPP. Previous studies have generally assumed a linear relationship between SIF and GPP at daily and longer time scales, but support for this assumption is lacking. Here, we used the GPP/SIF ratio to investigate seasonal variations in the relationship between SIF and GPP over the Northern Hemisphere (NH). Based on multiple SIF products and MODIS and FLUXCOM GPP data, we found strong seasonal hump‐shaped patterns for the GPP/SIF ratio over northern latitudes, with higher values in the summer than in the spring or autumn. This hump‐shaped GPP/SIF seasonal variation was confirmed by examining different SIF products and was evident for most vegetation types except evergreen broadleaf forests. The seasonal amplitude of the GPP/SIF ratio decreased from the boreal/arctic region to drylands and the tropics. For most of the NH, the lowest GPP/SIF values occurred in October or September, while the maximum GPP/SIF values were evident in June and July. The most pronounced seasonal amplitude of GPP/SIF occurred in intermediate temperature and precipitation ranges. GPP/SIF was positively related to temperature in the early and late parts of the growing season, but not during the peak growing months. These shifting relationships between temperature and GPP/SIF across different months appeared to play a key role in the seasonal dynamics of GPP/SIF. Several mechanisms may explain the patterns we observed, and future research encompassing a broad range of climate and vegetation settings is needed to improve our understanding of the spatial and temporal relationships between SIF and GPP. Nonetheless, the strong seasonal variation in GPP/SIF we identified highlights the importance of incorporating this behavior into SIF‐based GPP estimations.

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Spatio-temporal evolution and future scenario prediction of karst rocky desertification based on CA–Markov model - Fei Chen; Shijie Wang; Xiaoyong Bai; Fang Liu; Yichao Tian; Guangjie Luo; Qin Li; Jingfeng Wang; Luhua Wu; Yue Cao; Huiwen Li; Yuanhong Deng; et al. (Arabian Journal of Geosciences, 2021)

Perfusion microvessel density in the cerebral cortex of septic rats is negatively correlated with endothelial microparticles in circulating plasma - Zhenzhou Wang; Jingfeng Liu; Xi Liu; Xinjie Guo; Tian Li; Ran Pang; Meili Duan (Metabolic Brain Disease, 2021)

Assessment models and dynamic variables for dynamic life cycle assessment of buildings: a review - Shu Su; Huan Zhang; Jian Zuo; Xiaodong Li; Jingfeng Yuan (Environmental Science and Pollution Research, 2021)

Potential of hotspot solar‐induced chlorophyll fluorescence for better tracking terrestrial photosynthesis - Dalei Hao; Ghassem R. Asrar; Yelu Zeng; Xi Yang; Xing Li; Jingfeng Xiao; Kaiyu Guan; Jianguang Wen; Qing Xiao; Joseph A. Berry; Min Chen (Global Change Biology, 2021)
Remote sensing of solar‐induced fluorescence (SIF) opens a new window for quantifying a key ecological variable, the terrestrial ecosystem gross primary production (GPP), because of the revealed strong SIF–GPP correlation. However, similar to many other remotely sensed metrics, SIF observations suffer from the sun‐sensor geometry effects, which may have important impacts on the SIF–GPP relationship but remain poorly understood. Here we used remotely sensed SIF, globally distributed tower GPP data, and a mechanistic model to provide a systematic analysis. Our results reveal that leaf physiology, canopy structure, and sun‐sensor geometries all affect the SIF–GPP relationship. In particular, we found that SIF observations in the sun‐tracking hotspot direction can be a better proxy of GPP due to the similar responses of light use efficiency and SIF escaping probability in the hotspot direction to the increasing incoming solar radiation. Such conclusions are supported by a variety of modeling simulations and satellite observations over various plant function types, at different time scales and with satellite observational modes. This study demonstrates the potential and advantage of normalizing SIF observations to the hotspot direction for better global GPP estimations. This study also demonstrates the great potentials of current and future spaceborne sun‐tracking satellite missions for a significant improvement in measuring and monitoring, at a wide range of spatial and temporal scales, the changes in terrestrial ecosystem GPP in response to anticipated changes in the Earth's environmental conditions.

Moisture availability mediates the relationship between terrestrial gross primary production and solar‐induced chlorophyll fluorescence: Insights from global‐scale variations - Anping Chen; Jiafu Mao; Daniel Ricciuto; Jingfeng Xiao; Christian Frankenberg; Xing Li; Peter E. Thornton; Lianhong Gu; Alan K. Knapp (Global Change Biology, 2021)
Effective use of solar‐induced chlorophyll fluorescence (SIF) to estimate and monitor gross primary production (GPP) in terrestrial ecosystems requires a comprehensive understanding and quantification of the relationship between SIF and GPP. To date, this understanding is incomplete and somewhat controversial in the literature. Here we derived the GPP/SIF ratio from multiple data sources as a diagnostic metric to explore its global‐scale patterns of spatial variation and potential climatic dependence. We found that the growing season GPP/SIF ratio varied substantially across global land surfaces, with the highest ratios consistently found in boreal regions. Spatial variation in GPP/SIF was strongly modulated by climate variables. The most striking pattern was a consistent decrease in GPP/SIF from cold‐and‐wet climates to hot‐and‐dry climates. We propose that the reduction in GPP/SIF with decreasing moisture availability may be related to stomatal responses to aridity. Furthermore, we show that GPP/SIF can be empirically modeled from climate variables using a machine learning (random forest) framework, which can improve the modeling of ecosystem production and quantify its uncertainty in global terrestrial biosphere models. Our results point to the need for targeted field and experimental studies to better understand the patterns observed and to improve the modeling of the relationship between SIF and GPP over broad scales.

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Malnutrition worsens fluorosis-induced damage in hypothalamic-pituitary-ovarian axis of rats - Yongmei Liu; Ling Li; Jingfeng Xu; Siwen Yu; Shijun Wang; Maojuan Yu; Wenbing Zou; Mingliang Cheng; Shuhua Xia (Molecular & Cellular Toxicology, 2019)

Solar‐induced chlorophyll fluorescence exhibits a universal relationship with gross primary productivity across a wide variety of biomes - Jingfeng Xiao; Xing Li; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2019)

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Multiple hydrological models comparison and an improved Bayesian model averaging approach for ensemble prediction over semi-humid regions - Wenbo Huo; Zhijia Li; Jingfeng Wang; Cheng Yao; Ke Zhang; Yingchun Huang (Stochastic Environmental Research and Risk Assessment, 2019)

Solar‐induced chlorophyll fluorescence is strongly correlated with terrestrial photosynthesis for a wide variety of biomes: First global analysis based on OCO‐2 and flux tower observations - Xing Li; Jingfeng Xiao; Binbin He; M. Altaf Arain; Jason Beringer; Ankur R. Desai; Carmen Emmel; David Y. Hollinger; Alisa Krasnova; Ivan Mammarella; Steffen M. Noe; Penélope Serrano Ortiz; et al. (Global Change Biology, 2018)
Solar‐induced chlorophyll fluorescence (SIF) has been increasingly used as a proxy for terrestrial gross primary productivity (GPP). Previous work mainly evaluated the relationship between satellite‐observed SIF and gridded GPP products both based on coarse spatial resolutions. Finer resolution SIF (1.3 km × 2.25 km) measured from the Orbiting Carbon Observatory‐2 (OCO‐2) provides the first opportunity to examine the SIF–GPP relationship at the ecosystem scale using flux tower GPP data. However, it remains unclear how strong the relationship is for each biome and whether a robust, universal relationship exists across a variety of biomes. Here we conducted the first global analysis of the relationship between OCO‐2 SIF and tower GPP for a total of 64 flux sites across the globe encompassing eight major biomes. OCO‐2 SIF showed strong correlations with tower GPP at both midday and daily timescales, with the strongest relationship observed for daily SIF at the 757 nm ( R 2 = 0.72, p R 2 = 0.57–0.79, p R 2 = 0.16, p 4 grasslands and croplands than for C 3 ecosystems. The generally consistent slope of the relationship among biomes suggests a nearly universal rather than biome‐specific SIF–GPP relationship, and this finding is an important distinction and simplification compared to previous results. SIF was mainly driven by absorbed photosynthetically active radiation and was also influenced by environmental stresses (temperature and water stresses) that determine photosynthetic light use efficiency. OCO‐2 SIF generally had a better performance for predicting GPP than satellite‐derived vegetation indices and a light use efficiency model. The universal SIF–GPP relationship can potentially lead to more accurate GPP estimates regionally or globally. Our findings revealed the remarkable ability of finer resolution SIF observations from OCO‐2 and other new or future missions (e.g., TROPOMI, FLEX) for estimating terrestrial photosynthesis across a wide variety of biomes and identified their potential and limitations for ecosystem functioning and carbon cycle studies.

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Preparation, Gel Electrophoresis Analysis, and Nutritional Evaluation of a Functional Krill Protein Concentrate with Low Fluoride Level from Antarctic krill ( Euphausia superba ) - Li’ang Yin; Xiaoming Jiang; Yan Fan; Jingfeng Wang; Changhu Xue; Yong Xue (Journal of Aquatic Food Product Technology, 2017)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)

Tissue distribution of olive flounder VDAC2 and its expression in fish cell lines - Aijun Lü; Xiucai Hu; Li Li; Chao Pei; Chao Zhang; Xianglin Cao; Xianghui Kong; Guoxing Nie; Xuejun Li; Jingfeng Sun (Fish Physiology and Biochemistry, 2015)

Impacts of land-cover types on an urban heat island in Hangzhou, China - Li Sheng; Dengsheng Lu; Jingfeng Huang (International Journal of Remote Sensing, 2015)

Heavy metal flows in multi-resource utilization of high-alumina coal fly ash: a substance flow analysis - Chenjian Yu; Huiquan Li; Xiaoping Jia; Bo Chen; Qiang Li; Jingfeng Zhang (Clean Technologies and Environmental Policy, 2015)

Differences in sex reversion and growth between normal and neomale stock in half-smooth tongue sole, Cynoglossus semilaevis - Qiaomu Hu; Song-Lin Chen; Fengtao Gao; Yangzhen Li; Shanshan Liu; Feng Liu; Jingfeng Yang; Min Du (Aquaculture International, 2014)

Hpyerglycemic effect of a mixture of sea cucumber and cordyceps sinensis in streptozotocin-induced diabetic rat - Shiwei Hu; Jingfeng Wang; Zhaojie Li; Jia Fu; Yuming Wang; Changhu Xue (Journal of Ocean University of China, 2014)

Diversity and structure of bacterial communities in Fildes Peninsula, King George Island - Jingfeng Fan; Lili Li; Junli Han; Hongxia Ming; Jiangyu Li; Guangshui Na; Jiaying Chen (Polar Biology, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)

Survival and development of Liaodong oak stump sprouts in the Huanglong Mountains of China six years after three partial harvests - Li Rong; Zhang Wenhui; He Jingfeng; Zhou Jianyun (New Forests, 2013)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)

Trophic states of creeks and their relationship to changes in water level in Xixi National Wetland Park, China - Yufeng Li; Hongyu Liu; Jingfeng Hao; Nan Zheng; Xiao Cao (Environmental Monitoring and Assessment, 2012)

Development and evaluation of a new detection tool—visual DNA microarray for simultaneous and specific detection of human immunodeficiency virus type-1 and hepatitis C virus - Jingfeng Tang; Li Zhou; Lian Lian Duan; Yang Feng; Xuan Cao; Yefu Wang (Molecular Biology Reports, 2011)

Overexpression of miR-22 reverses paclitaxel-induced chemoresistance through activation of PTEN signaling in p53-mutated colon cancer cells - Jian Li; Yangde Zhang; Jingfeng Zhao; Fangren Kong; Yuxiang Chen (Molecular and Cellular Biochemistry, 2011)

Forms and balance of nitrogen and phosphorus in cage culture waters in Guangdong Province, China - Yanmao Wen; Xiange Wei; Tingfei Shu; Jingfeng Zhou; Guanghui Yu; Feng Li; Yanyun Huang (Chinese Geographical Science, 2007)

CIS – Cloning of Identical Sequences Between Two Complex Genomes - Veronika Zabarovska; Jingfeng Li; Olga Muravenko; Ludmila Fedorova; Eleonora Braga; Ingemar Ernberg; Claes Wahlestedt; George Klein; Eugene R. Zabarovsky (Chromosome Research, 2000)